2003
DOI: 10.1023/b:jocm.0000032720.02801.e6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Impedance based indices of cardiac contractility in dogs

Abstract: ACI and the Heather index were the most reliable impedance derived indices of cardiac contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…PEP, measured in milliseconds (ms), was computed as the time interval between maximum depolarization of left ventricular (R peak on EA ECG beat) and opening of the aortic valve (B point on EA ICG beat) (Seery et al, 2016). HI, measured as ( dZ/dt ) max /RC in ohm/sec 2 , was computed as ratio of maximum amplitude of ICG representing maximum blood velocity in aorta (amplitude of C point on EA ICG beat), and time interval between R peak and C point on EA ECG and ICG beats respectively (Peng et al, 2004). Figure 1b depicts the measurements of PEP and HI via synchronized ECG and ICG waveforms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PEP, measured in milliseconds (ms), was computed as the time interval between maximum depolarization of left ventricular (R peak on EA ECG beat) and opening of the aortic valve (B point on EA ICG beat) (Seery et al, 2016). HI, measured as ( dZ/dt ) max /RC in ohm/sec 2 , was computed as ratio of maximum amplitude of ICG representing maximum blood velocity in aorta (amplitude of C point on EA ICG beat), and time interval between R peak and C point on EA ECG and ICG beats respectively (Peng et al, 2004). Figure 1b depicts the measurements of PEP and HI via synchronized ECG and ICG waveforms.…”
Section: Methodsmentioning
confidence: 99%
“…The HI approximates the blood acceleration in the aorta during systole, and is measured in units of ohm/sec 2 (Baker et al, 1983). More recently, HI has been measured as ( dZ / dt ) max /RC (Peng et al, 2004), which has the advantage of the ease in the detection of R peak on the ECG signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than using the differential of the transthoracic bioimpedance signal (dZ/dt) to derive stroke volume the Aesculon uses the second derivative. A study that used an animal flow probe model to investigate the bioimpedance method showed that the second differential of the bioimpedance waveform, or acceleration index (ACI), was better correlated to equivalent aortic flow probe variables than was cardiac output (n = 16 dogs) [14], providing some rational for the Aesculon's new approach to bioimpedance signal analysis. Wong and colleagues studied 35 children, 11 of whom needed prolonged critical asthma therapy.…”
Section: Evaluation Of Haemodynamic Alterations and Fluid Responsivenessmentioning
confidence: 99%
“…The electrical impedance cardiography, one of the plethysmography, has been extensively applied to assess cardiac parameters, because of its minimal invasiveness of nature. The stroke volume, cardiac output, diastolic filling, ventricular contractility, and so forth, have been evaluated using this impedance plethysmography in previous literature [1][2][3][4][5]. According to the electrode arrangement and location, there are three most popular electrical impedance technologies applied for non-invasively assessing cardiac pumping function.…”
Section: Introductionmentioning
confidence: 99%